Analysis the relationship between tone of financial report and audit risk (Journal of Economic Research & Business Administration, 2020)
Nowadays, in the competitive environment, to conduct a high-quality audit, auditors try to use anyavailable information. The audit quality depends on the amount of audit risk that determines the effortsof the audit company. In this regard, the task of finding additional factors that have a significant impacton the audit risk evaluation comes to the fore. One of the factors that influence on audit risk evaluationand risk management is the tone of financial reports. Based on the use of content analysis, regressionanalysis, this article checks whether the linguistic tone used for corporate annual reports is related to thelevel of audit risk. The model is based on previous studies factors determining audit risk, with the inclusionof new variable characterizing an optimistic or negative report tone. We find that annual reportswith positive tone are associated with a lower audit risk, suggesting that the tone of the annual reportmay be considered as a factor to assess audit risk. In general, the data obtained indicate that auditorscan improve their methods of assessing audit risks by systematically taking into account the linguisticqualitative characteristics of financial statement disclosures.